2021
DOI: 10.1093/molbev/msab298
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably LowKIRandHLADiversity in Amerindians Reveals Signatures of Strong Purifying Selection Shaping the CentromericKIRRegion

Abstract: The killer-cell immunoglobulin-like receptors (KIR) recognize human leukocyte antigen (HLA) molecules to regulate the cytotoxic and inflammatory responses of natural killer cells. KIR genes are encoded by a rapidly evolving gene family on chromosome 19 and present an unusual variation of presence and absence of genes and high allelic diversity. Although many studies have associated KIR polymorphism with susceptibility to several diseases over the last decades, the high-resolution allele-level haplotypes have o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 136 publications
(185 reference statements)
3
17
1
Order By: Relevance
“…Vargas et al 38 suggest a population‐specific manner of allelic pairwise LD. To better understand KIR allelic associations and patterns in Bulgarians, we have estimated the pairwise linkage disequilibrium for the 10 KIR loci.…”
Section: Discussionmentioning
confidence: 99%
“…Vargas et al 38 suggest a population‐specific manner of allelic pairwise LD. To better understand KIR allelic associations and patterns in Bulgarians, we have estimated the pairwise linkage disequilibrium for the 10 KIR loci.…”
Section: Discussionmentioning
confidence: 99%
“…However, in modern humans, KIR interaction with HLA-C is the only KIR/HLA interaction present in every individual, with rare exceptions highly prone to virus infections. 128 Low frequency of KIR interactions with HLA-A or -B in Amerindians 129 suggest KIR interactions with HLA-C may now have a greater impact on human survival than those with HLA-A and -B.…”
Section: Rapid Evolution Of Kir and Hlamentioning
confidence: 99%
“…Balancing selection embodies frequency fluctuations of genetic variants accompanying the relative selective advantage of their respective phenotypes. In this respect, KIR-A haplotypes have arisen to very high frequency in East Asian and Amerindian populations through positive natural selection, 41,129,142,143 presumably in response to specific pathogens. However Hiby et al 135 first noticed that the preeclampsia pregnancy syndrome is most prevalent in women who are homozygous for KIR-A and who also carry a C2-ligand fetus.…”
Section: Evolution Of Interactions Between Kir and Hla Class Imentioning
confidence: 99%
See 1 more Smart Citation
“…18 Highresolution studies have revealed enormous KIR allelic diversity across human populations, likely rivaling that of HLA. [19][20][21][22][23][24][25][26][27][28][29] Although this diversity is especially evident in groups representing the deep population structure of the African continent, previous studies have focused on sub-Saharan Africa. [24][25][26] To counter lack of knowledge concerning immunogenomic diversity in Northern Africa, we focus here on a population from Egypt.…”
Section: Introductionmentioning
confidence: 99%